Exact relativistic models of thin disks around static black holes in a magnetic field (2014)
The exact superposition of a central static black hole with surrounding thin disk in presence of a magnetic field is investigated. We consider two models of disk, one of infinite extension based on a Kuzmin-Chazy-Curzon metric and other finite based on the first Morgan-Morgan disk. We also analyze a simple model of active galactic nuclei (AGN) consisting of black hole, a Kuzmin-Chazy-Curzon disk and two rods representing jets, in presence of magnetic field. To explain the stability of the disks, we consider the matter of the disk made of two pressureless streams of counter-rotating charged particles (counter-rotating model) moving along electrogeodesic. Using the Rayleigh criterion, we derivate for circular orbits the stability conditions of the particles of the streams. The influence of the magnetic field on the matter properties of the disk and on its stability are also analyzed. © World Scientific Publishing Company.